Uncommon Somatic Mutations in Metastatic NUT Midline Carcinoma. (November 2017) - Cavalieri, Stefano; Stathis, Anastasios; Fabbri, Alessandra; Sonzogni, Angelica; Perrone, Federica; Tamborini, Elena; Pelosi, Giuseppe; de Braud, Filippo; Platania, Marco
Introduction: NUT midline carcinoma (NMC) is a rare and aggressive epithelial cancer arising from median organs. It is driven by chromosomal translocation t(15;19) involving the rearrangement of NUT (nuclear protein in testis) and BRD4 (bromodomain 4) genes leading to fusion oncoprotein BRD4-NUT. Case presentation: We report the case of a woman who was previously treated with induction chemotherapy, surgery, radiotherapy and adjuvant trastuzumab for HER-2 positive invasive ductal carcinoma of the breast. After 6 months of follow-up a lung nodule appeared. A biopsy showed an adenocarcinoma fetal type/lung blastoma, so a left inferior lobectomy was performed: NMC harboring BRD4-NUT rearrangement was diagnosed. After 9 months of follow-up, bone and soft tissue metastases occurred, so the patient was given radiotherapy. Next-generation sequencing technology identified somatic mutations in deleted in colorectal cancer (DCC), mixed lineage leukemia protein 3 (MLL3), and splicing factor 3B subunit 1 (SF3B1) genes in NMC cells from both primitive cancer and metastases. The patient was treated with the experimental BRD4 inhibitor for 10 months, until the disease progressed to the lung and bone. After spinal cord compression, the patient was offered palliative radiotherapy to bone and eventually died aged 39 years. Conclusions: To the best of our knowledge, our case is the first DCC, MLL3, and SF3B1 mutated NUT midline carcinoma reported in the literature. If these mutations were confirmed to play a role in this neoplasm, clinical trials analyzing targeted therapies should be considered, eg. colorectal cancer-like chemotherapies for DCC mutations, hypomethylating agents for MLL3 mutations or SF3B1 inhibitors in case of specific somatic mutations.